2019
DOI: 10.1051/meca/2018051
|View full text |Cite
|
Sign up to set email alerts
|

Fault detection of damper in railway vehicle suspension based on the cross-correlation analysis of bogie accelerations

Abstract: Nowadays, the condition-based maintenance is associated more and more with railway transport to improve the safety, availability, reliability and capacity of this transport system, and to reduce life cycle costs for the railway vehicles. The condition-based maintenance requires that vehicle components are replaced based on their real condition, which implies the fault detection and isolation during the train's operation. The paper proposes a method to detect the failure of the damper in the primary suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The RMS acceleration is also marked on the diagrams. In all the cases presented, it is observed that the RMS The accelerometers were mounted on a side of the bogie as follows: one accelerometer on each axle box and one accelerometer on the bogie frame against each axle (Figures 2 and 3) [30][31].…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMS acceleration is also marked on the diagrams. In all the cases presented, it is observed that the RMS The accelerometers were mounted on a side of the bogie as follows: one accelerometer on each axle box and one accelerometer on the bogie frame against each axle (Figures 2 and 3) [30][31].…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…Recent studies, based on the measured data or numerical simulations, have shown that the vehicle dynamic response is correlated with the track irregularities [10,13,[27][28][29], which creates the premises of developing certain monitoring methods of track quality or the vehicle condition [30]. The correlation method has been used to highlight the connection between the lateral and vertical axle box acceleration and differently processed track geometry parameters,…”
mentioning
confidence: 99%
“…The data-driven approach does not rely on vehicle simulation models but requires historical tracking data and prior training. As shown in Table 1, the data-driven approaches with different strategies for FD/I of railway vehicle suspensions over the past two decades can be mainly classified into four sub-categories: (1) (1) SM-based [29][30][31][32][33][34][35]: A classical SM-based approach used in RVSFD is based on the cross-correlation function. In [29], the cross-correlation function between the accelerations of two bogies was applied to determine the health conditions of vehicle suspension systems.…”
Section: Data-driven Approachmentioning
confidence: 99%
“…The issue of the damping asymmetry of the railway vehicles suspension has been mainly addressed from the perspective of detecting and identifying the suspension defects, a technique known as condition monitoring [5][6][7][8][9][10]. Many research studies in this regard is being developed using model-based methods where the asymmetry of the suspension damping is included, such as interacting multiple-model algorithm [11,12], functional model method [13], evaluating estimation residuals [14], system dynamic interactions method [15][16][17], cross-correlation analysis based method [18][19][20].…”
Section: Introductionmentioning
confidence: 99%